448 Struma ovarii: a rare ovarian malignancy masquerading as a dermoid cyst. A case report. (13th November 2020) - Addley, S; Mihai, R; Alazzam, M; Dhar, S; Soleymani majd, H
Abstract : Introduction: Struma ovarii (SO) is rare, accounting for 0.3–1% of ovarian tumours. So is defined histologically as replacement of at least 50% of the ovarian tissue by thyroid tissue. Malignant transformation occurs in less than 5% of cases, most often into a papillary thyroid carcinoma (PTC). An association with a synchronous cancer of the thyroid gland proper exists. Methods: We present a case of malignant struma ovarii - considering presentation, diagnosis, management and follow-up. Results: A 75 year-old presented with the incidental finding of an ovarian mass on imaging. Pre-operative CA125 was 38 and CT described a 9 cm dermoid cyst. The patient underwent TAH, BSO and omentectomy. Final histopathology reported struma ovarii with co-existing papillary thyroid carcinoma. Post-operative CT confirmed FIGO stage 1A disease. Adjuvant thyroidectomy and radio-active iodine ablation (RAI) therapy were recommended by the multi-disciplinary team (MDT). The patient remained under follow-up, incorporating long-term thyroid-stimulating hormone (TSH) suppression and surveillance of serum thyroglobulin – with no recurrence to date. Conclusions: Patients with malignant SO usually present with non-specific symptoms and early stage disease. Very few cases are identified pre-operatively due lack of characteristic features on imaging, with the most common mis-diagnosis being that of a dermoid cyst. CA 125 has no role. Fertility-sparing surgery, pelvic clearance, thyroidectomy and radio-active iodine ablation therapy have all been described in the management of malignant struma ovarii.